KESEJAHTERAAN SUBYEKTIF MENURUT KI AGENG SURYOMENTARAM (KASM) DALAM PERSPEKTIF PSIKOLOGI KONTEMPORER - - Sumanto (Buletin Psikologi, 2011)
Psychology has come to understand quite a bit in how people survive and endure under condition of adversity. Psychologists tend to develop subjective well‐being concepts focusing on risk of psychopathology and unhappiness problems. The such paper is an effort to balance trend of subjective well being studies by introducing subjective well being concepts that not only based on hedonic viewpoint (deleting elation problems) but also eudaimonic as well, in order to help people to be happy at any time, any situation, any condition and preventing them waste of their time and energy to gain the goals, where, in the end, it can not give what they want. In 1928 Ki Ageng Suryomentaram, one of the Indonesian pionir psychologists, introduced his well‐being concept stressing on developing positive mental attitude preventing uncontrolled human expectation that is able to expand and able to shrink. According to him, what actually make people happy is not because of what are people responded but how people respond them. Also, understanding ones dan others feeling is very important for everyone in pursuing well‐being. In fact, his approaches to well‐being study are on the level with the sophisticated modern psychology ones.